REGULASI EMOSI DALAM MENYELESAIKAN PERMASALAHAN PADA REMAJA - Janah, Maslichah Raichatul (Universitas Sahid Surakarta, 2015)
AbstractEmotion regulation are well entrenched in vocational students gave a positive significance . From the research that see that future development of adolescents in this age emotions greatly affect its development . So it appears that both the juvenile form of aggression and bullying behavior influenced of low emotion regulation.The importance of emotion regulation that are embedded in the vocational students , at an early stage will help in increasing achievement motivation . Emotion regulation are embedded with both the need for help from parents in doing good parenting and the existence of a supportive environmentTo be able to develop the analysis it is necessary to study the effect of free school policy as a management strategy in the development of vocational schools in Sukoharjo in order to create the hyuman resources ExcellenceKey word:Emotional Regulation, Problem Solving, adolescents